The role of periostin (OSF-2) in the cytoadherence phenomena mediated by malaria parasites - Phong, Zhi-Ying; Chin, Joo-Yie; Ng, Yee Ling; Zakaria, Nurul Izza; Athirah-Azman, Siti Nur; Kosaisavee, Varakorn; Rénia, Laurent; Lee, Wenn-Chyau (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe pathogenesis of severe malaria is primarily attributed to the cytoadherence properties of Plasmodium-infected erythrocytes (IRBC), which include rosetting and IRBC-endothelial cytoadherence. These cytoadherence events are influenced by various parasite- and host-derived factors. Previously, antibodies against human periostin (OSF-2), an inflammation-associated protein, were reported to inhibit rosetting. In this study, we aimed to characterize the OSF-2-mediated cytoadherence in infections caused by Plasmodium falciparum (the most fatal human malaria parasite) and P. knowlesi (an emerging, potentially fatal zoonotic malaria parasite).MethodsLaboratory-adapted P. falciparum and P. knowlesi isolates were cultured, and the late-stage parasites were purified for experiments using recombinant human OSF-2.ResultsWe found that OSF-2 at a concentration of 200 ng/ml induced rosette-stimulation in both parasite species. Furthermore, we demonstrated the serum dependency of OSF-2-mediated rosetting. The rosette-stimulating effect of OSF-2 was completely abolished when IRBC were treated with a low concentration of trypsin. This suggests a role for P. falciparum erythrocyte membrane protein 1 (PfEMP1) in OSF-2-mediated rosetting by P. falciparum, and reveals the trypsin-sensitive nature of the P. knowlesi-derived ligands involved in OSF-2-mediated rosetting. We also found that OSF-2-mediated rosetting was independent of the ABO blood group. Additionally, we demonstrated the ability of OSF-2 to disrupt the IRBC-endothelial binding.DiscussionThis work contributes to our understanding of the host-parasite interactions in malaria pathobiology.